2018
DOI: 10.3390/publications6030031
|View full text |Cite
|
Sign up to set email alerts
|

The UK Scholarly Communication Licence: Attempting to Cut through the Gordian Knot of the Complexities of Funder Mandates, Publisher Embargoes and Researcher Caution in Achieving Open Access

Abstract: Whilst take-up of open access (OA) in the UK is growing rapidly due partly to a number of funder mandates, managing the complexities of balancing compliance with these mandates against restrictive publisher policies and ingrained academic priorities, has resulted in UK higher education institutions (HEIs) often struggling with confused researchers, complex workflows, and rising costs. In order to try to address this situation, the UK Scholarly Communication Licence (UK-SCL) was formulated to bypass the root ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…Detractors to OA mandates are many, with journal editorials often decrying them as hurting academic freedom and the ability of journals and publishers to properly function (Johnston, 2017). Others have reported on the difficulty in managing mandates, especially as researchers often fall under multiple mandates from their institutions, various grant funders, and more (Baldwin & Pinfield, 2018). Still other studies have found that a mandate on its own is often not enough; faculty, for various reasons, do not always comply, meaning that other peopleoften librarians-must do work to ensure their faculty members' research is deposited into an appropriate repository (Xia et al, 2012;Zhang et al, 2015).…”
Section: Benefits and Drawbacksmentioning
confidence: 99%
“…Detractors to OA mandates are many, with journal editorials often decrying them as hurting academic freedom and the ability of journals and publishers to properly function (Johnston, 2017). Others have reported on the difficulty in managing mandates, especially as researchers often fall under multiple mandates from their institutions, various grant funders, and more (Baldwin & Pinfield, 2018). Still other studies have found that a mandate on its own is often not enough; faculty, for various reasons, do not always comply, meaning that other peopleoften librarians-must do work to ensure their faculty members' research is deposited into an appropriate repository (Xia et al, 2012;Zhang et al, 2015).…”
Section: Benefits and Drawbacksmentioning
confidence: 99%
“…The development of the OA has given way to the definition of policies in HEIs. The analyses performed and trends in policy development for OA promotion [45], knowledge communication [31], open courses [25], and commercial exploitation of research results [53].…”
Section: Policiesmentioning
confidence: 99%
“…In [31], the authors analyze the use and implementation of the UK Scholarly Communication Licensing policy (UK-SCL) as a strategy that encourages OA and allows control of the content produced in HEIs. The results identify perceived benefits in helping authors gain control of their publications, disseminate publications rapidly and widely, and reduce costs at institutions.…”
Section: Policiesmentioning
confidence: 99%
See 1 more Smart Citation
“…While there is no doubt that CC licenses are still a useful solution in many cases of data publishing, some challenges exist for handling non-copyrighted data. Some proposals have recently been pushed forward (e.g., UK Scholarly communication license (Baldwin, J. and Pinfield, S., 2018) and Microsoft Open Use of Data Agreement (https://github. com/microsoft/Open-Use-of-Data-Agreement)).…”
Section: Literature Reviewmentioning
confidence: 99%